Reevaluating hikikomori and challenging loneliness assumptions in Japan: A cross-sectional analysis of a nationwide internet sample - Yong, Roseline (Frontiers in Psychiatry, 2024)
Introduction Loneliness in Japan, accentuated by demographic challenges and the hikikomori phenomenon (extreme social withdrawal), has raised concerns. This study critically examines loneliness dynamics, questioning assumptions embedded in hikikomori classifications. The term “hikikomori,” originally signifying prolonged home stay, requires nuanced exploration, especially regarding outgoing behaviors’ relationship with loneliness. Objectives Investigating the intricate connection between outgoing behaviors and loneliness, this study questions the effectiveness of existing hikikomori classifications. Aiming to understand if these classifications accurately represent the loneliness spectrum across age groups, the research emphasizes the significance of comprehending loneliness dynamics amid societal challenges. The study explores an array of factors influencing loneliness, including demographics, mental health, and outgoing behaviors, advocating for a reassessment of assumptions linked to hikikomori classifications. Methods This secondary analysis employed data from a nationwide Internet addiction survey conducted in July 2012. A sample of 623 participants, representative of Japanese internet users aged 16 and above, was included for analysis. Loneliness was assessed using the UCLA Loneliness Scale, and exposure variables included demographic, mental health, outgoing behaviors, and lifestyle factors. Statistical analyses encompassed descriptive statistics, one-way ANOVA, chi-square tests, and logistic regression. Results Significant differences were observed in loneliness scores based on sex, age, marital status, employment, and outgoing behaviors. Mental health factors, including dissatisfaction with life and romance, life stress, and psychological distress, emerged as strong contributors to loneliness. The study challenges existing hikikomori classifications, suggesting they may not fully encapsulate the loneliness experiences of individuals engaged in routine school or work activities. Conclusion Findings underscore the need for a reevaluation of hikikomori, emphasizing loneliness as a complex and multifaceted issue in Japan. The study advocates for nuanced strategies to address loneliness, considering diverse demographic vulnerabilities. Limitations include the pre-pandemic sample and potential unmeasured confounding factors.